(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Medical Sociology is "the study of health care as it is institutionalized in a society and of health, or illness and its relationship to social factors". Migration is the term used to describe the temporary or permanent relocation of a person’s usual place of living across space during a given period. This study focuses on international return migration, defined as returning to one’s country of citizenship after being an international migrant abroad for at least a year. Aims: to evaluate the respondents’ socioeconomic status and to know the health and socio-economic problems or challenges faced by return migrants at the time of return. Methods: 100 participants were surveyed using planned interviews and observation as part of the current study’s information collection process. Through purposeful sampling, the respondents were selected. Results: The results showed that most respondents (43%) are between the ages of 51 and 60 years; 64% of respondents are men; 56% of respondents identify as Hindu; 39% of respondents are undergraduates; and 82 % of the respondents are married and according to second objective the findings are as follows, the majority (41%) of the respondents faced food & water and economic problems, 94.50% of the respondents replied that the cause of hardship of women is a problem to breech privacy and protection and 82.75% of the respondents faced isolation as a psychological issue.